Age and growth of blue spot mullet, Valamugil seheli (Forskal) from Mangalore - Moorthy, K S Venkatesha; Reddy, H R V; Annappaswamy, T S (Indian Journal of Fisheries, 2011)
Length-weight relationship, condition, age and growth and mortality rates of Valamugil seheli from Mangalore region were studied during April 1998 and March 1999. The combined length-weight relationship derived was log W = - 1.4257+2.6207 logL and the growth was found to be allometric. Seasonal variation in condition factor showed higher values from September to December, while the mean values of Kn showed an increasing trend with size. Studies on age and growth revealed that males grow faster than females and the von- Bertalanffy growth equation was Lt = 601.76 [l-e -0.2309(t+0.6934)] for males and Lt = 534.53 [l-e -0.2853(t+0.5632)] for females. The instantaneous total, natural and fishing mortality were found to be 1.5060, 0.9713 and 0.5347 for males and 1.3384, 0.9004 and 0.4380 for females respectively.